ACCORDANCE PROVIDING PRINCIPLES OF ACADEMIC AVIATION TRAINING TO EASA PART-66 AND EASA PART-147 BASIC TRAINING REQUIREMENTS - Орлов, О.; Зімін, В.; Тризна, О. (Proceedings of National Aviation University (archive), 2012)
Main regulation aspects of EASA maintenance training standards implementation in activity of aviationacademic/educational training institutions are considered and analysed. Recommendation and proposals for adaptationactions of such training institutions are formulated with respect to conditions and peculiarities of their functioning inUkraine. Some adaptive measures for academic aviation institutions are proposed. It based on existing conditions andtakes into account the peculiarities of the forerun maintenance training evolution in Ukraine. The recommendations onregulatory policy during implementation of EASA standards to Civil Aviation Authorities of Ukraine are provided